Induced pluripotent stem cells: based cancer immunotherapy - Pinheiro, Mariana Sofia Carvalho (2022)
Cancer is still one of the leading causes of death worldwide, mainly due to its resistance to current treatments. Recent studies have shown that embryonic stem cells (ESC) and tumor cells share some characteristics such as similar antigens, angiogenic growth factors and also lead to cell apoptosis. These findings suggest that ESC can be used as immunizing factors to promote antitumor responses. In this work, TNGA cells were used, a mouse embryonic stem cell (mESC) cell line, which were subjected to different culture conditions in order to try to obtain ground and primed pluripotency states. For this, three fundamental pluripotency factors, LIF and two inhibitors, PD and CHIR, were used. Initially, the objective was to evaluate the morphology of cells when subjected to different stimuli, and it was verified that, when subjected to medium with LIF and 2i, the cells reached a ground state of pluripotency and, when the 2i was removed, the cells reverted to a primed state of differentiation. In addition to this evaluation, 7 different genes were analyzed by RT-qPCR which, in previous RNA-seq analyses, showed to be more expressed when cells started differentiating processes and, therefore, may have relevance as possible new tumor antigens. The results confirmed that all genes have a higher expression under LIF conditions. Western-Blot assays were also performed to assess the expression of Nanog, a pluripotency marker, in cells under different conditions, verifying that its expression is increased under pluripotency stimuli (LIF/2i). To complement these results, transfection assays were carried out on some of the genes analyzed, to see if they certainly have any influence in promoting cell differentiation, and for the c-Myc gene silencing, the results showed an increase in the number of cells that reversed differentiation processes. A proteomics analysis was also performed comparing the breast cancer cell line, E0771, to TNGA cells in different culture conditions, although the results were not conclusive, there was verified a tendency towards the similarity between the patterns of primed TNGA cells and the tumor cell line. Some of the results obtained confirmed the existing bibliography, being promising for this study area but, however it is necessary to repeat some assays and carry out additional studies to understand if these tested genes are safe and if they can promote an immune response in an organism.